Nonsurgical Chin and Jawline Augmentation Using Calcium Hydroxylapatite and Hyaluronic Acid Fillers - Moradi, Amir; Shirazi, Azadeh; David, Roy (Facial Plastic Surgery, 2019)
The shape of the jawline from the mandibular angle to its most forward point at the chin has a profound effect on an individual's appearance and is an area of concern for many seeking esthetic procedures. Dermal filler injections alone or in combination with other modalities, such as skin tightening energy devices, allow enhancement of the jawline while avoiding the need for surgical procedures. The authors introduce new anatomical zones and nomenclature to enhance safety and outcome when enhancing the jawline. Cadaver dissections were performed to better understand landmarks and potential risks and a topographic guide proposed to assist clinicians to create an esthetically pleasing jawline. Techniques for jawline rejuvenation with calcium hydroxylapatite (CaHA) and high G prime hyaluronic acid (HA) fillers are described. When considered as an esthetic unit, the jawline can be broken down into masseteric, buccal, and mental zones, each with their own injection protocols and safety considerations. Dermal fillers suitable for jawline rejuvenation include either CaHA with or without integral lidocaine, a high G prime HA filler, or a hybrid mixture of CaHA and HA, depending on the desired esthetic outcome and the individual's needs. Small volumes of product per injection point achieve the most natural esthetic outcome and minimize serious adverse events. With these techniques, the angle of the mandible is better defined, the pre- and postjowl hollows are filled, and as a result the jawline appears visibly straighter. CaHA and high G prime HA fillers are effective nonsurgical treatments for redefining the mandibular angle and straightening the contour of the jaw. For optimal results, the jawline should be considered as an esthetic unit and careful consideration paid to anatomical landmarks that influence efficacy and safety.
Keywords: calcium hydroxylapatite; chin; hyaluronic acid fillers; jawline; rejuvenation